2021
DOI: 10.3390/jdb9040054
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Aspects of SARS-CoV-2, Potential Role of Exosomes and Their Impact on the Human Transcriptome

Abstract: With over 4.8 million deaths within 2 years, time is of the essence in combating COVID-19. The infection now shows devastating impacts on the younger population, who were not previously predicted to be vulnerable, such as in the older population. COVID-19-related complications have been reported in neonates whose mothers were infected with SARS-CoV-2 during pregnancy, and in children who get infected. Hence, a deeper understanding of the pathophysiology of COVID-19 during various developmental stages and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 153 publications
0
6
0
Order By: Relevance
“…Subsequently, MVBs fuse with the plasma membrane resulting in the release of exosomes into the extracellular environment ( Johnstone et al., 1987 ; Trams et al., 1981 ). Nevertheless, exosomes are merely a subset of secretory EVs, other particles include—but are not limited to—apoptotic, micro-, onco-vesicles ( Kalluri and LeBleu, 2020 ; Kowal et al., 2014 ; Raposo and Stoorvogel, 2013 ), and exosome-like enveloped viruses ( Dogra et al., 2021 ). Accumulating evidence show that while all EVs carry molecular footprints from their cell of origin, exosomes selectively package proteins, nucleic acids, and do not appear enriched in cellular debris ( Kowal et al., 2014 ; Lotvall et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, MVBs fuse with the plasma membrane resulting in the release of exosomes into the extracellular environment ( Johnstone et al., 1987 ; Trams et al., 1981 ). Nevertheless, exosomes are merely a subset of secretory EVs, other particles include—but are not limited to—apoptotic, micro-, onco-vesicles ( Kalluri and LeBleu, 2020 ; Kowal et al., 2014 ; Raposo and Stoorvogel, 2013 ), and exosome-like enveloped viruses ( Dogra et al., 2021 ). Accumulating evidence show that while all EVs carry molecular footprints from their cell of origin, exosomes selectively package proteins, nucleic acids, and do not appear enriched in cellular debris ( Kowal et al., 2014 ; Lotvall et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The viruses must also be considered as a subset of the vast EVP canopy ( Ghosh et al, 2020 ; Dogra et al, 2021 ). Many viruses follow the late lysosome or multivesicular body (MVB) followed by exocytosis mechanism for egress ( Alem et al, 2021 ; Dogra et al, 2021 ; Elmore et al, 2021 ). As shown by Dogra et al (202 1) the biogenesis of SARS-coV-2 have an egress pathway identical to the exosomes.…”
Section: Extracellular Vesicles Particles and Their Subtypesmentioning
confidence: 99%
“…Many viruses follow the late lysosome or multivesicular body (MVB) followed by exocytosis mechanism for egress ( Alem et al, 2021 ; Dogra et al, 2021 ; Elmore et al, 2021 ). As shown by Dogra et al (202 1) the biogenesis of SARS-coV-2 have an egress pathway identical to the exosomes. While, other viruses, such as HIV, pinch off the plasma membrane ( Brügger et al, 2006 ).…”
Section: Extracellular Vesicles Particles and Their Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was suggested that congenital SARS-CoV-2 infection during early pregnancy could potentially trigger neurodevelopmental complications [ 178 ], no supporting evidence has been reported, so far. Furthermore, it was established that pregnant women are less likely to contract SARS-CoV-2 than the general public [ 189 ], and that the likelihood of SARS-CoV-2 vertical transmission is low [ 190 , 191 , 192 , 193 , 194 , 195 ]. For example, only 5.7% of 176 neonatal SARS-CoV-2 infections cases were classified as confirmed congenital infections [ 196 ].…”
Section: Covid-19 During Early Pregnancymentioning
confidence: 99%